Effect of Integrated Yoga Modules and Satvic Diet on Selected Risk Factors Among Men Cancer Patients - Duraisami, V.; Mohana Krishnan, Prof. R. (Journal of Neonatal Surgery, 2025)
Finding the impact of combined yoga modules and a sattvic diet on specific risk variables in male cancer patients was the aim of the current investigation 40 male cancer patients were divided into two groups for the study: the experimental group and the control group. There were twenty male cancer patients in the experimental group while the control group received no training of any kind; they practiced the Pawanamuktasana series, asana, pranayama, meditation, and relaxation for six weeks. Standardized tests were used to measure the physiological variable (systolic blood pressure) before and after the experiment. After analyzing the data using Analysis of Covariance (ANCOVA), it was determined that among male cancer patients, the Pawanamuktasana series, asana, pranayama, meditation, and relaxation had a significant (P < 0.05) impact on the physiological variable (systolic blood pressure).